ホッキョクイキ タイリュウケン オヨビ カブ セイソウケン ニ オケル ニサンカタンソ ノウド ノ コウクウキ カンソク - 町田, 敏暢; マチダ, トシノブ; Maksyutov, Shamil; 菅原, 敏; スガワラ, サトシ; 森本, 真司; モリモト, シンジ; Machida, Toshinobu; Sugawara, Satoshi; Morimoto, Shinji (2002)
P(論文) 1998年の3月に実施された北極圏航空機観測計画（Arctic Airborne Measurement Program 1998; AAMP 98）において航空機にCO2濃度連続観測装置を搭載し，北極域対流圏及び下部成層圏におけるCO2濃度の空間分布を観測した. CO2濃度は下部成層圏において高度と共に急激に減少する鉛直勾配が存在しているが対流圏においては鉛直方向の濃度勾配は非常に小さかった． 下部成層圏における水平分布においては緯度方向にCO2濃度の系統的な勾配は見られなかったが，78°-80°Nにおいて水平飛行中に極めて高濃度のCO2が観測された． このことから，等圧面上であってもCO2濃度の分布が水平方向に大きく異なる場合のあることが明らかになった． 本観測で得られたCO2濃度とO3 濃度は非常に良い負の相関を示す． これは濃度の空間分布が主に空気塊の混合に支配されていることを表している． Tropospheric and lower stratospheric CO2 mixing ratios were measured onboard an aircraft in the Arctic Airborne Measurement Program 1998. Steep vertical gradients in CO2 mixing ratio were observed in the lower stratosphere. Small gradients were seen in the troposphere, reflecting weak sources and sinks for CO2 in winter. A significant increase in CO2 mixing ratio was found during level flight in the lower stratosphere. Back trajectory analysis indicated that rapid upward transport brought high CO2 to the observation area. Spatial variations of CO2 mixing ratio were highly correlated with O3 mixing ratio. It is suggested that CO2 distribution was produced mainly by air transport and mixing. departmental bulletin paper